Self-Efficacy Scales In Online Learning: Construction And Validation - Suci Nurhayati; Sugilar (Universitas Pendidikan Ganesha, 2023)
Low enthusiasm and student learning outcomes during the online learning process are influenced by several factors, one of which is the self-efficacy factor. The reality on the ground shows that teachers have not been able to measure students' self-efficacy level during the online learning process, so this research was conducted to develop and validate items that assess four sources of self-efficacy in online learning. This research belongs to the type of development research carried out through the literature review stage, deriving instrument items, testing instruments on samples, selecting instrument items, and analyzing the reliability and validity of the instrument. The subjects involved in this research were one expert in educational evaluation, one in online learning, and 176 students. Data collection in the study was carried out using the non-test method, with research instruments in the form of instrument validity sheets and student self-efficacy questionnaires. The data obtained in the study were then analyzed by testing the validity and reliability of the instrument items using partial least squares (PLS) analysis. The research analysis results show that the instrument developed has achieved valid and reliable values for thirteen items on self-efficacy measurement in online learning, so this instrument can be used in research involving self-efficacy as a variable that has shown four sources/dimensions of self-efficacy.